2015
DOI: 10.4081/jlimnol.2015.1305
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton biodiversity and community structure vary along spatiotemporal environmental gradients in restored peridunal ponds

Abstract: Zooplankton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The structure of the rotifer metacommunity in the ponds seems to be determined by environmental factors acting at the local scale rather than by spatial factors related to regional-scale processes such as dispersal, which is in line with previous studies conducted at comparable spatial scales ( Waterkeyn et al ., 2008 ; Antón-Pardo et al ., 2015 ). The explained variance analysis indicated that niche processes seem to prevail in structuring the rotifer assemblage in spring, with habitat filters selecting different rotifer genera in each pond.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the rotifer metacommunity in the ponds seems to be determined by environmental factors acting at the local scale rather than by spatial factors related to regional-scale processes such as dispersal, which is in line with previous studies conducted at comparable spatial scales ( Waterkeyn et al ., 2008 ; Antón-Pardo et al ., 2015 ). The explained variance analysis indicated that niche processes seem to prevail in structuring the rotifer assemblage in spring, with habitat filters selecting different rotifer genera in each pond.…”
Section: Discussionmentioning
confidence: 99%
“…In La Pletera salt marshes, there is a short distance between the new lagoons and the existing ones, facilitating the colonization of the new lagoons. Antón-Pardo et al (2016) mention that the short distance among the lagoons and the apparent absence of geographical barriers facilitate the occurrence of zooplankton dispersal vectors (e.g., waterbirds, wind or humans). Other studies performed on permanent and temporary lagoons showed a similar pattern to that found in the La Pletera salt marshes (Cottenie et al, 2003;Audet et al, 2013;Antón-Pardo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton assemblages respond rapidly to variations in environmental factors such as those caused by hydrological instability in Mediterranean coastal ecosystems (Quintana et al, 1998a(Quintana et al, , 1998bBrucet et al, 2005;Badosa et al, 2006;Olmo et al, 2016). However, other factors or processes such as dispersal ability or priority effects also affect the colonization dynamics and, consequently, the zooplankton composition of restored wetlands (Bilton et al, 2001;Cohen & Shurin, 2003;Ortells et al, 2012;Antón-Pardo et al, 2016). These assemblages are dominated by passive dispersers that are characterized by a high dispersal ability by wind or bird transport (but see Incagnone et al, 2015); thus, they rapidly colonize new water bodies (Louette & De Meester, 2005;Frisch et al, 2006;Olmo et al, 2012;Audet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Large fractions of unexplained community variation remain, however, suggesting an important role for the elements of chance or randomness (Jeffries 1989). Stochastic processes and priority effects are expected to be strong at the beginning of the hydroperiod due to egg-bank hatching, before abiotic and biotic sorting of species can effectively act as filters in structuring local communities (Antón-Pardo et al 2016;Castillo-Escrivà et al 2017c;Mahaut et al 2018). This results in increased unexplained variation, with model residuals accounting for a higher proportion in the tropical metacommunity, probably related to its higher species richness, but also because of lower limnological heterogeneity (Leibold and Chase 2018), as shown by the homogeneity test of multivariate dispersion.…”
Section: Discussionmentioning
confidence: 99%